Feasibility and acceptability of a pilot, peer-led HIV self-testing intervention in a hyperendemic fishing community in rural Uganda - Matovu, Joseph K. B.; Bogart, Laura M.; Nakabugo, Jennifer; Kagaayi, Joseph; Serwadda, David; Wanyenze, Rhoda K.; Ko, Albert I.; Kurth, Ann E. (PloS one, 2020)
Novel interventions are needed to reach young people and adult men with HIV services given the low HIV testing rates in these population sub-groups. We assessed the feasibility and acceptability of a peer-led oral HIV self-testing (HIVST) intervention in Kasensero, a hyperendemic fishing community (HIV prevalence: 37–41%) in Rakai, Uganda. Methods This study was conducted among young people (15–24 years) and adult men (25+ years) between May and August 2019. The study entailed distribution of HIVST kits by trained “peer-leaders,” who were selected from existing social networks and trained in HIVST distribution processes. Peer-leaders received up to 10 kits to distribute to eligible social network members (i.e. aged 15–24 years if young people or 25+ years if adult man, not tested in the past 3 months, and HIV-negative or of unknown HIV status at enrolment). The intervention was evaluated against the feasibility benchmark of 70% of peer-leaders distributing up to 70% of the kits that they received; and the acceptability benchmark of >80% of the respondents self-testing for HIV. Results Of 298 enrolled into the study at baseline, 56.4% (n = 168) were young people (15–24 years) and 43.6% (n = 130) were adult males (25+ years). Peer-leaders received 298 kits and distributed 296 (99.3%) kits to their social network members. Of the 282 interviewed at follow-up, 98.2% (n = 277) reported that they used the HIVST kits
Keywords: Pilot; HIV self-testing; Hyperendemic fishing community; Rural Uganda